Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pengunjung Pada Caffe Paimo Malang (Studi Kasus Pada Pengunjung Caffe Paimo Malang) - Cahyudi Ardiansya Usman; Budi Wahono; M. Khoirul Anwarudin Broto Suharto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine and analyze whether there is an influence between service quality and price on visitor satisfaction at Caffe Paimo Malang. This type of research is intended to provide an explanation of the causal relationship between variables through hypothesis testing, making it an explanatory research to provide an explanation through the previously formulated problem, objectives to be achieved, and hypothesis testing. Therefore, the method used in this research is a survey method. The data processed in this study is the result of distributing questionnaires to customers who have visited and made purchases at Caffe Paimo Malang over a period of 4 months, totaling 95 respondents. This method implies that the study samples from the population and uses a questionnaire (list of questions) as the primary data collection instrument. In addition, in-depth interviews were also conducted to supplement the required data. The research findings show that the results of the t-test (partial) on service quality have an effect on visitor satisfaction, as indicated by a t-value of 3.732, and price has an effect on visitor satisfaction, as indicated by a t-value of 5.160. Meanwhile, the results of the F-test indicate a calculated value of 0.000, which is less than 0.05. This means that service quality and price simultaneously influence visitor satisfaction among customers of Caffe Paimo Malang. Based on the coefficient of determination calculation, the Adjusted R Square is 73%, while the remaining 27% can be explained by variables not covered in this study.Top of Form Keywords : Service Quality, Price and Visitor Satisfaction.